Experimental study on flame tilt angles of two unequal fires in a longitudinal ventilated tunnel. (July 2023) - Wei, Shuqi; Wan, Huaxian; Zhou, Xiaohui; Zhang, Yuchun
Graphical abstract: Highlights: Burning behavior of two unequal fires in a ventilated tunnel is conducted. Effects of fire loads, separation distance and ventilation velocity is explored. Buoyance force, ventilation force and pressure thrust between fires are quantified. Differences of flame heights and tilt angles of two unequal fires are analyzed. Correlations for flame tilt angles of two fires in ventilated tunnel are proposed. Abstract: In historical tunnel fire accidents causing major casualties and property losses, the special fire phenomenon of multiple fires burning was usually accompanied. Other than the longitudinal ventilation in tunnel, the interaction burning of multiple fires will also make the flame tilt. Flame tilt angle is an important parameter to characterize the magnitude of acting forces on fires and it determines the possibility of ignition and flame spread. Former studies were mainly focused on multiple equal fires with same sizes, very limited attention has been paid on multiple unequal fires. Due to the different air entrainment mechanisms, the proposed correlations for flame tilt angle of multiple equal fires might be unsuitable for the multiple unequal fires. This paper presents an experimental study on flame tilt angles of two unequal square gaseous fires of propane in a 1/10 scale tunnel with longitudinal ventilation. Two square burners with different side lengths were located parallel and along the longitudinal centerline of tunnel. The effects of heat release rate of each burner, the burner edge spacing and the ventilation velocity were explored. Using the image processing method, the flame heights and tilt angles of upstream fire and downstream fire were determined. The results showed that due to the shielding effect of upstream fire acting on the downstream fire, the flame height of downstream fire is larger than the upstream fire, while the flame tilt angle of downstream fire is lower than the upstream fire. In addition, the flame heights of upstream and downstream fires are reduced with increasing the ventilation velocity, while the flame height of downstream fire is weakly affected by the separation distance. As the ventilation velocity increases, both the upstream and downstream flame tilt angles increase first and then maintain unchanged. The separation distance has little influence on the upstream flame tilt angle, while it affects the downstream fire more. Among the impact factors, the longitudinal ventilation plays a leading role of the flame tilt behaviors of two fires in tunnel. Based on the force analysis, it is found that the pressure thrust between two fires is much smaller than the buoyancy force and ventilation force. As a result, different correlations for predicting the flame tilt angles of two unequal fires in tunnel are developed based on the coupling effect of buoyancy force and ventilation force of each fire.